Os desafios da organização do patrimônio documental arquivístico nos equipamentos culturais da Universidade Federal do Ceará - Teixeira, Marcela Gonçalves (2015)
It presents the results of research that aims to investigate how the Federal University of Ceará (UFC) is dealing with documentary heritage archival of its cultural facilities in view of the preservation of historical memory and the dissemination and access of this documentary heritage of Ceará community and other interested parties. Methodologically, it is a survey of descriptive exploratory, adopting primary and secondary documentary sources for the survey and analysis of the state of the art relating to the subject matter. Data collection was done by simple direct observation and questionnaire addressed to staff working in cultural facilities of UFC Campus of Fortaleza. The survey was conducted in three stages: the first consisted of literature review; in the second stage, did the mapping of cultural facilities of UFC and, finally, the empirical study of some managers and professionals working in the archives, as well as the management of these cultural facilities. We understand the cultural facilities included in this research are spaces practices, artistic and cultural production, created and consolidated through legal acts of the Upper Management, which also have staff in their performance units. As results of the mapping, we found the UFC ten (10) equipment, legally institutionalized, which have peculiarities, both in regard to archival documentary heritage as much as the organization of these collections. It also became evident that the actions relating to the conservation and dissemination of the history and university culture are still tenuous for the recognition of the institution and its community identity, even if they already are apparent that these devices are in essence memory spaces of the Federal University Ceara. With regard to treatment and informational organization of these documents the initiatives are isolated and therefore do not meet the criteria established by Conarq, specifically the File Document Management System of the Federal Public Administration (SIGA) and also by the Computerized System Document Archival management (SIGAD). Given these results, we suggest that creates mechanisms that may contribute to the development of a policy file at the Federal University of Ceará.